Reflections on Risk Analysis, Screening, and Contested Rationalities - Manning, Peter K. (Canadian journal of criminology and criminal justice, 2006)
The concept of risk and modelling it (imagining possible outcomes with negative consequences) has a long history in social science and crisis management. Risk lies in the shadow between the known and the unknown. This article reflects discussions of low-probability, high-cost events such as those reflected in the conventional tactics associated with terrorism. Risks and fear of them are shaped extraordinarily by 'big bang events' such as 9/11, and these shape imagined future deciding, prevention tactics, and organizational routines. Short-time crisis deciding is guided inordinately by 'group effects,' pressure for consensus, and action over cogitation, difference, and muddling through. The attraction of risk analysis to security matters is clear: It makes simple decisions that are not. It easily fits with the technological conceit that assumes electronic-computer-based surveillance, artifice, and models can reduce human judgement to questions easily answered by a computer with a database. It enables a front stage of statistical rational planning and execution of policies that fail but permit backstage manipulations, profit taking, and obfuscation of matters of human judgement. (English) [ABSTRACT FROM AUTHOR]